Implementation of Modified AES as Image Encryption Scheme - Heidilyn V Gamido; Ariel M Sison; Ruji P Medina (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
Since images have bigger size than text, a faster encryption algorithm is needed to provide higher security in digital images. The paper presents a modified AES algorithm that address the requirement in image encryption. The modified algorithm used bit permutation in replacement of MixColumns to reduce the computational requirement of the algorithm in encrypting images. Results of the study show that the modified algorithm exhibited faster encryption and decryption time in images. The modified algorithm also achieved a good result in the key sensitivity analysis, histogram analysis, information entropy, the correlation coefficient of adjacent pixels, Number of Pixel Change Rate and Unified Average Change Intensity making the modified algorithm resistant to statistical and differential attack.